Austudy 1987 to 1997 : the effect of Commonwealth income support on educational participation - Walker, Agnes, 1942-; Johnson, Peter; Osei, Kwabena; University of Canberra. National Centre for Social and Economic Modelling; Australia. Department of Education, Training and Youth Affairs (Bruce, ACT : NATSEM, 2001)
The Commonwealth Government has traditionally provided support for the further education of Australian students. For example, the Tertiary Education Assistance Scheme (TEAS), which operated between 1974 and 1986, was replaced by AUSTUDY (1987-97). AUSTUDY was replaced in 1998 by the current scheme, Youth Allowance.While all three schemes had the same broad goal of assisting those undertaking post-compulsory studies, during the TEAS period the financial values of the grants were increasingly reduced and assistance was restricted to students from low income families (DEET 1988, p. 17). Transitions from one scheme to the next were relatively smooth, with minor adjustments in policy settings having been frequently made both between schemes and while each scheme was operating. An assessment of TEAS was undertaken by the Department of Employment, Education and Training (DEET 1988).
"June 2001".
Bibliography: p. 59-60.
Also available online via the World Wide Web.
Keywords: AUSTUDY; Student aid -- Australia